RANCANG BANGUN SISTEM CASE BASED REASONING UNTUK TINDAK KEJAHATAN SESUAI BAB 19, 20, 21 KUHP (Universitas Palangka Raya, 2017)
Violations of crime in Indonesia are frequent today, not excluding criminal offenses againstbodies and lives that are set out in chapters 19, 20 and 21 of the Criminal Code. For a person whoworks in the legal field, data violation of the law that has occurred is needed in carrying out hisduties later. Past data can be used as a reference and consideration to deal with the same cases thatmay occur in the future.This knowledge based system will be built by applying the case based reasoning method.This method will take the solution of the previous cases that will be used to provide information tothe new problem.This system will produce results in the form of information submitted articles, prosecutions,and sentences based on the specification of criminal offenses entered into the user's system. Thisoutput is taken from past case information similar to the new case